Optimising Natural Bait Selection for Sustainable Handline Fishing: Behavioural Phase Analysis of Juvenile Barramundi (Lates calcarifer) in Response to Bait Type and Body Size - Septiyani, Anita; Fuad, Fuad; Wiadnya, Dewa Gede Raka; Nurdiani, Rahmi; Hariati, Anik Martinah (Graduate School, Universitas Brawijaya, 2025)
Understanding the natural bait preference of predatory fish, such as barramundi, plays a crucial role in improving capture efficiency. This knowledge also supports sustainable fisheries by optimizing bait selection for handline fishing and reducing reef damage by active gear where barramundi species commonly live. This study examines the response of barramundi to various types of natural bait and investigates whether body size plays a significant role in this response. Predatory fish are divided into three different sizes (9, 13, and 15 cm total length), with each size having nine replicates. Fishing behavior and response to baits were divided into four phases: arousal, searching, finding, and uptake. Kinovea computer software (www.kinovea.org) was used to identify each phase with visual support from iVcam. The experiment was designed using a 54 L aquarium filled with saline water of 32 ppt. Data were analyzed using one-way ANOVA in SPSS version 26. When significant differences (p<0.05) were found, Tukey's post hoc test was performed. Bait from trash fish and shrimps did not show significant differences (p>0.05). Worms provided the fewest responses on times and behavior. Body size did not significantly affect behavioral responses or response times (p > 0.05). In conclusion, bait type significantly influenced barramundi's responses, with worms eliciting a significantly slower response compared to shrimp and trash fish, which were equally effective.